Pengaruh Safety Climate Terhadap Kecelakaan Kerja Dengan Safety Behavior Sebagai Variabel Intervening Pada Karyawan PT. Panca Wana Indonesia Di Krian - Mohammad Agus Setiawan; Tri Siwi Agustina (Universitas Airlangga, 2014)
This study aims to analyze the effect of safety climate on job accident at employees of PT. Panca Wana Indonesia with safety behavior as intervening variable. The research was conducted on supervisor and employees at operational and production department with a sample of 87 persons. The analysis technique used is a path analysis. The independent variable in this research is the safety climate (X), is the intervening variable safety behavior (Z), and the dependent variable is job accident (Y). Results of this study indicate that safety climate has direct effect and significant on job accident is proved, because it has a significance value (Sig) t 0,000 less than the significance level (α) of 5% t, and safety climate is proved has a effect on job accident with safety behavior as intervening variable, because the value of significance (Sig) t variable safety climate to safety behavior, and safety behavior to job accident are 0,000, is smaller than the value significance level (α) by 5%.